CXC motif chemokine receptor 4 gene polymorphism and cancer risk. Issue 49 (December 2016) - Wu, Yang; Zhang, Chun; Xu, Weizhang; Zhang, Jianzhong; Zheng, Yuxiao; Lu, Zipeng; Liu, Dongfang; Jiang, Kuirong
Abstract: Background: Previous epidemiological studies have reported the relationship between CXC motif chemokine receptor 4 ( CXCR4 ) synonymous polymorphism (rs2228014), and risk of cancer, but the results remained conflicting and controversial. Therefore, this study was devised to evaluate the genetic effects of the rs2228014 polymorphism on cancer risk in a large meta-analysis. Methods: The computer-based databases (EMBASE, Web of Science, and PubMed) were searched for all relevant studies evaluating rs2228014 and susceptibility to cancer. In the analysis, pooled odds ratios (ORs) with its corresponding 95% confidence intervals (CIs) were calculated in 5 genetic models to assess the genetic risk. Egger regression and Begg funnel plots test were conducted to appraise the publication bias. Results: Data on rs2228014 polymorphism and overall cancer risk were available for 3684 cancer patients and 5114 healthy controls participating in 11 studies. Overall, a significantly increased risk of cancer was associated with rs2228014 polymorphism in homozygote model (OR = 2.01, 95% CI: 1.22–3.33) and in recessive model (OR = 1.97, 95% CI: 1.23–3.16). When stratified by ethnicity, the results were positive only in Asian populations (heterozygote model: OR = 1.36, 95% CI: 1.13–1.65; homozygote model: OR = 2.43, 95% CI: 1.21–4.91; dominant model: OR = 1.47, 95% CI: 1.13–1.90; recessive model: OR = 2.25, 95% CI: 1.13–4.48; and allele model: OR = 1.48, 95% CI: 1.10–1.99). Besides, in the subgroup analysis by source of control, the result was significant only in population-based control (homozygote model: OR = 2.39, 95% CI: 1.06–5.40; recessive model: pooled OR = 2.24, 95% CI: 1.02–4.96). Conclusion: In general, our results first indicated that the rs2228014 polymorphism in CXCR4 gene is correlated with an increased risk of cancer, especially among Asian ethnicity. Large, well-designed epidemiological studies are required to verify the current findings.